The role of ultraviolet colour in the assessment of mimetic accuracy between Batesian mimics and their models: a case study using ant-mimicking spiders - Corcobado, Guadalupe; Herberstein, Marie E; Pekár, Stano (Die Naturwissenschaften, 2016)
The use of ultraviolet (UV) cues for intra- and inter-specific communication is common in many animal species. Still, the role of UV signals under some predator-prey contexts, such as Batesian mimicry, is not clear. Batesian mimicry is a defensive strategy by which a palatable species (the mimic) resembles an unpalatable or noxious species (the model) to avoid predation. This strategy has evolved independently in many different taxa that are predated by species capable of UV perception. Moreover, there is considerable variation in how accurately Batesian mimics resemble their models across species. Our aim was to investigate how UV colour contributed to mimetic accuracy using several ant-mimicking spider species as a case study. We measured the reflectance spectrum (300-700 nm) for several species of mimics and models, and we tested whether they differ in visible and UV colour. We modelled whether two different predators could discriminate between mimics and models using colour information. We found that generally, ant-mimicking spiders differed significantly from their ant models in UV colour and that information from the visible range of light cannot be extrapolated into the UV. Our modelling suggested that wasps should be able to discriminate between mimics and models combining information from visible and the UV light, whereas birds may not discriminate between them. Thus, we show that UV colour can influence mimic accuracy and we discuss its potential role in Batesian mimicry. We conclude that colour, especially in the UV range, should be taken into account when measuring mimetic accuracy.
Keywords: Adaptation, Biological; Visual signals; Myrmecomorphy; pavouci; Inter-specific animal communication; Batesian mimicry; mimikry; biologická adaptace; Animals; Ultraviolet Rays; Imperfect mimicry; Biological Mimicry; zvířata; Ants; Spiders; ultrafialové záření; Formicidae